2014
DOI: 10.1371/journal.pone.0087343
|View full text |Cite
|
Sign up to set email alerts
|

Roles of PPARγ/NF-κB Signaling Pathway in the Pathogenesis of Intrahepatic Cholestasis of Pregnancy

Abstract: BackgroundIntrahepatic cholestasis of pregnancy (ICP) is the most prevalent pregnancy specific liver disease. However, the pathogenesis and etiology of ICP is poorly understood.AimTo assess the expression of peroxisome proliferator-activated receptorγ (PPARγ) and nuclear factor kappa B (NF-κB) in placenta and HTR-8/SVneo cell, and evaluate the serum levels of cytokines, bile acids, hepatic function and lipids in control and ICP patients and the fetal outcome, in order to explore the role of PPARγ/NF-κB signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 71 publications
3
52
0
Order By: Relevance
“…Subsequently, IκBα is degraded from NF‐κB and ubiquitinated, which enables the activation and the translocation of NF‐κB to enter the nucleus to further activate gene transcription . Evidence shows that NF‐κB is activated during the formation process of cholestasis . In our present study, the subunit of NF‐κB is studied to determine whether PLP plays the regulation role in NF‐κB and the results showed that PLP at high (80 g/kg) and middle (40 g/kg) dose significantly reduced the mRNA and protein expression levels of p65, whereas doses of 20 g/kg had a weaker effect.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Subsequently, IκBα is degraded from NF‐κB and ubiquitinated, which enables the activation and the translocation of NF‐κB to enter the nucleus to further activate gene transcription . Evidence shows that NF‐κB is activated during the formation process of cholestasis . In our present study, the subunit of NF‐κB is studied to determine whether PLP plays the regulation role in NF‐κB and the results showed that PLP at high (80 g/kg) and middle (40 g/kg) dose significantly reduced the mRNA and protein expression levels of p65, whereas doses of 20 g/kg had a weaker effect.…”
Section: Discussionmentioning
confidence: 75%
“…[36] Evidence shows that NF-jB is activated during the formation process of cholestasis. [37] In our present study, the subunit of NF-jB is studied to determine whether PLP plays the regulation role in NF-jB and the results showed that PLP at high (80 g/kg) and middle (40 g/kg) dose significantly reduced the mRNA and protein expression levels of p65, whereas doses of 20 g/kg had a weaker effect. To further investigate the PLP effect on NF-jB pathway, we examined the upstream activators of the NF-jB, IKK level on mRNA expression and p-IKK level of protein expression.…”
Section: Discussionmentioning
confidence: 81%
“…Our study indicated that the activation of NF-κB induced by silencing IκBα enhanced the activity of Brg1 in cardiomyocyte, as well as the expression of TGF-β 1 in cardiac fibroblasts. In addition, a growing number of studies have highlighted the interaction of PPARγ and NF-κB [37,38], in which PPARγ could inhibit NF-κB activation via several mechanisms and then repress NF-κB-mediated transcription for certain inducible gene. In our study, the activation of PPARγ by rosiglitazone significantly inhibited the expression of NF-κB in cardiac fibroblasts and cardiomyocyte, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Women with ICP have an imbalance in the immune response to pregnancy. Zhang et al () found that ICP is associated with suppression of the Th2 immune response, resulting in increases of proinflammatory cytokine levels. Increased cytokine production is a factor in the etiology of gestational diabetes and preeclampsia (Zhang et al., ).…”
Section: A Complex Disordermentioning
confidence: 99%
“…Zhang et al () found that ICP is associated with suppression of the Th2 immune response, resulting in increases of proinflammatory cytokine levels. Increased cytokine production is a factor in the etiology of gestational diabetes and preeclampsia (Zhang et al., ). This may explain why women with ICP are more likely to experience these comorbidities (Shemer, Marschall, Ludvigsson, & Stephansson, ).…”
Section: A Complex Disordermentioning
confidence: 99%